2023
DOI: 10.1021/acs.jpclett.3c00765
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Three-Dimensional Structure of the c-KIT Proto-Oncogene Promoter and the Dynamics of Its Strongly Coupled Guanine Quadruplexes

Abstract: Guanine quadruplexes (G4s) play essential protective and regulatory roles within cells, influencing gene expression. In several gene-promoter regions, multiple G4-forming sequences are in close proximity and may form three-dimensional arrangements. We analyze the interplay among the three neighboring G4s in the c-KIT proto-oncogene promoter (WK1, WSP, and WK2). We highlight that the three G4s are structurally linked and their cross-talk favors the formation of a parallel structure for WSP. Relying on all-atom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…41 In contrast, c-Kit1 is one of three G4-forming sequences located in the promoter region of the proto-oncogene KIT, which encodes a tyrosine kinase receptor known to be a clinically validated target for treating different tumors. 42,43 In this way, we can first assess whether our compounds exhibit a preference for G4s over B-DNA, and also determine if they have an affinity for a specific G4 topology.…”
Section: Catalytic Nadh Oxidationmentioning
confidence: 99%
“…41 In contrast, c-Kit1 is one of three G4-forming sequences located in the promoter region of the proto-oncogene KIT, which encodes a tyrosine kinase receptor known to be a clinically validated target for treating different tumors. 42,43 In this way, we can first assess whether our compounds exhibit a preference for G4s over B-DNA, and also determine if they have an affinity for a specific G4 topology.…”
Section: Catalytic Nadh Oxidationmentioning
confidence: 99%
“…Consequently, anticancer drugs that target G4 are actively being pursued with a number in clinical trials approved, , while there is also interest in developing diagnostic molecular probes to recognize these structures . The diversity of oncogene targets is further evidenced by their ability to form coupled ternary structures. , While, recent studies have revealed the presence of quadruplex forming sequences in Gram-negative bacteria suggesting a possible avenue to develop G4 targeting antibiotics to tackle antimicrobial resistance . Additionally, the presence of G4 structures in viral genomes, including RNA viruses and SARS-CoV-2 makes, further highlights its potential as a therapeutic target. , …”
Section: Introductionmentioning
confidence: 99%
“… 18 The diversity of oncogene targets is further evidenced by their ability to form coupled ternary structures. 19 , 20 While, recent studies have revealed the presence of quadruplex forming sequences in Gram-negative bacteria suggesting a possible avenue to develop G4 targeting antibiotics to tackle antimicrobial resistance. 21 Additionally, the presence of G4 structures in viral genomes, including RNA viruses and SARS-CoV-2 makes, further highlights its potential as a therapeutic target.…”
Section: Introductionmentioning
confidence: 99%